A quantitative and dynamic risk analysis tool for offshore well construction & repair - Miura, K.; Morooka, C. K.; Mendes, J. R.P.; Guilherme, I. R. [UNESP] (My University, 2005)
The main concern of activities developed in oil & gas well construction is safety. But safety during the well construction process is not a trivial subject. During the well construction, the process transforms the context itself. Actual risk evaluation approaches focus on operational tasks on existent systems, like production plants, and they are based in static analyses of those. In other words, those approaches don't allow a dynamic analysis that evaluates the risk for each alteration of the context. The present paper presents a new methodology for both dynamic and quantitative risk analysis of well construction process. Moreover, it presents a prototype tool developed to support this methodology. With the use of this tool operational risk levels for each moment during well construction can be obtained, without a great effort of professional planning. By this approach, active barriers for each programmed activity can be quantified, given an initial situation. In this way, the dynamic analysis of amount of safety barriers during the well construction process can be easily obtained.